2019
DOI: 10.1111/and.13454
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E administration does not ameliorate tramadol‐associated impairment of testicular function in Wistar rats

Abstract: Tramadol is widely abused in Nigeria and has been reported to cause fertility decline via testicular oxidative stress. This study investigated the effect of vitamin E, an antioxidant on some reproductive parameters in male Wistar rats administered tramadol. Twenty male Wistar rats (180-200 g) were randomly assigned into four groups (n = 5) thus: Control (0.2 ml vehicle: olive oil), tramadol-treated (20 mg/kg of tramadol), vitamin E-treated (100 mg/kg of vitamin E) and tramadol + vitamin Etreated (received tram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Supporting our finding, the tramadol-treated female rats had lower estrogen levels in their serum, whereas the tramadol/vitamin C and tramadol/vitamin E treated groups had significantly higher levels 56 . In agreement with the previous studies, it has been found that opioids reduced serum testosterone levels in both rats, mice, and humans 1 , 63 – 67 . Histopathological investigation of tramadol-treated rabbit testes demonstrated vacuolization and the presence of disrupted immature spermatozoid.…”
Section: Discussionsupporting
confidence: 92%
“…Supporting our finding, the tramadol-treated female rats had lower estrogen levels in their serum, whereas the tramadol/vitamin C and tramadol/vitamin E treated groups had significantly higher levels 56 . In agreement with the previous studies, it has been found that opioids reduced serum testosterone levels in both rats, mice, and humans 1 , 63 – 67 . Histopathological investigation of tramadol-treated rabbit testes demonstrated vacuolization and the presence of disrupted immature spermatozoid.…”
Section: Discussionsupporting
confidence: 92%
“…24 However, another animal study reported that reduced sperm counts in rats treated with tramadol were not related to oxidative stress but rather to decreased T, FSH, and LH. 25 From accumulated pieces of evidence, tramadol addiction possibly harms male fertility, although further studies on human subjects are needed.…”
Section: Tramadolmentioning
confidence: 99%
“…The reduction in the number of germ cells in the seminiferous tubules corresponds to a decrease in the diameter of the seminiferous tubules. Thus, measurement of this diameter can be used to quantify spermatogenic function inside the testes and is easy to perform (Ameli et al, 2018;Udefa et al, 2020). For evaluation of the destruction and recovery period of spermatogenic function, the percentage of tubules with spermatogenic cells is also a useful tool.…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan-induced testicular injury mouse models are commonly used for experiments on spermatogonial stem cell transplantation, treatments for azoospermia due to spermatogenic failure and preserving male fertility after chemotherapy, in which evaluating spermatogenic function is essential (Ganguli et al, 2016;Sharma et al, 2019;Zhao et al, 2020). To evaluate spermatogenic function after busulfan treatment, several parameters, including the testicle-to-body weight ratio, percentage of tubules with spermatogenic cells and seminiferous tubule diameter, have been used (Karna et al, 2019;Udefa et al, 2020;Yang et al, 2019). However, all of these parameters have the same limitations.…”
Section: Introductionmentioning
confidence: 99%